Work-related injuries and its associated risk among staff in a Malaysian Public University - Ahmed, Shalaw Faris (2016)
Work-related injuries (WRIs) are injuries that occur at the workplace or that occur while commuting. WRI is still one of the occupational issues in the workplace, according to the Department of Occupational Safety and Health Malaysia (DOSH). There is multiple risk factors could cause WRI. WRI is usually studied in the dangerous sectors, but WRI among staff of the university setting in Malaysia is scarce. The main objective of this study was to determine the proportion of work-related injuries and its associated factors among staff of the Faculty of Medicine and Health Sciences (FMHS). A cross-sectional study was conducted on 364 randomly selected Malaysian employees who worked for at least one year in the faculty. The self-administered questionnaire was used to collect information on socio-demographic, employment and individual characteristics, as well as data on work-related injuries, occurred in the past 12 months. Data were analyzed by using the IBM Statistical Package of Social Sciences (SPSS) version 21. The results of the study showed that out of 317 respondents who answered the questionnaire and seventeen of them (5.4%) had experienced WRI, which the most common body parts injured were upper limbs (38.6%). Chi square test showed that factors were significantly associated with WRIs: job title (X2=9.351, df=1, p=0.002), feeling sleepy at work (X2=11. 012, df=1, p=0.001) and feeling fatigued at work (X2=5.903, df=1, p=0.015). Multiple logistic regression test showed the significant risk factors for WRIs were job title (OR=8.053, 95% CI: 2.022-32.076), part-time work (OR=6.657, 95% CI: 2.129- 20.818) and feeling sleepy at work (OR=4.519, 95% CI: 1.126-18.137). In conclusion, the proportion of WRI among the university employees is high compared to those in other countries. Based on the findings of this study, future research is needed to find out why the employee in this institution need to do part-time work that will leave them feeling sleepy at work and eventually exposed them to higher risk of getting WRIs.